Geomorphological Approach for Regional Zoning In The Merapi Volcanic Area - Langgeng Wahyu Santosa; Sutikno Sutikno (Indonesian Journal of Geography, 2006)
Geomorphologial approach can be used as the basic for identifying and analyzing the natural resources potentials, especially in volcanic landscape. Based on its geomorphology, Merapi volcanic landscape can be divided into 5 morphological units, i.e.: volcanic cone, volcanic slope, volcanic foot, volcanic foot plain, and fluvio-volcanic plain. Each of these morphological units has specific characteristic and natural resources potential. Based on the condition of geomorphology, the regional zoning can be compiled to support the land use planning and to maintain the conservation of environmental function in the Merapi Volcanic area.